Profile evaluation of patients diagnosed with non-neoplastic proliferative lesions in a dentistry clinic - Gabriela Medeiros da Cruz; Samuel Trezena; Sabina Pena Borges Pêgo; Lívia Máris Ribeiro Paranaíba; Daniella Reis Barbosa Martelli; Mario Rodrigues de Melo Filho (Universidade Estadual de Campinas, 2019)
Non-neoplastic proliferative lesions (NNPLs) are alterations that affect oral mucosal tissues. The etiology of these lesions is associated with local irritant processes, principally inflammation, infections and mechanical irritants. NNPLs are classified into four groups: inflammatory fibrous hyperplasia, pyogenic granuloma, peripheral ossifying fibroma, and peripheral giant cell lesion. Aim: This cross-sectional, quantitative, retrospective, analytical, informative and educational study aimed to evaluate the profiles of patients who were diagnosed with any non-neoplastic proliferative lesion in the Unimontes Stomatology Clinic, Brazil. Methods: From January 2001 to June 2012, 1505 patients were counted who underwent anatomopathological examination, in addition to evaluations for other conditions. Results: Of these 1505 patients, 223 were diagnosed with some type of non-neoplastic proliferative lesion, and statistical analysis showed that 76% were female and 24% male and that 23.3% were between 41 and 50 years of age. Inflammatory fibrous hyperplasia was the most common NNPL (86.5%). Conclusion: Due to the high frequency of these lesions in the dental clinic, this type of survey has significant relevance for informing health professionals about these proliferative processes. This information is necessary, since the dentist is intimately involved in both the etiology, treatment and prevention of these lesions.